How life context affects entrepreneurs' passion and performance - Stefan Schulte-Holthaus; Andreas Kuckertz (Review of Managerial Science, 2023)
This article examines the influence of the life context on entrepreneurial passion (EP) and performance. Drawing on the person–environment fit theory, we developed a model showing how the life context fit affects EP in the domains of founding, inventing, and developing and how this translates into performance. Using partial least squares structural equation modeling, we tested our hypotheses using a sample of 406 entrepreneurs from the cultural and creative industries. Due to the presence of unobserved heterogeneity in the overall sample, we conducted prediction-oriented segmentation, which revealed four segments in which life contexts exhibit not only positive but also adverse effects on EP. Our results showed that, in contrast to the extant literature, EP generates its overall effect on performance at the intersection of positively and negatively acting domains of founding, inventing, and developing. To explain the structural relations between the four segments, we conducted qualitative post hoc analyses to evaluate idiosyncratic data on passion and the life context and aligned our insights with the extant literature delineating four categories of entrepreneurs from the cultural and creative industries: artepreneurs, culturepreneurs, creative entrepreneurs, and lifestyle entrepreneurs. Our findings contribute to overcoming the dichotomy between passion as a personality trait and a dynamic construct and to understanding passion as an individual phenomenon with multiple sources that interacts with the proximal environment and that can impact entrepreneurial performance both positively and negatively. We extend the entrepreneurship and psychology literature, facilitating people's abilities to lead more entrepreneurial and passionate lives.
Keywords: L26; L82; Z11; 650; Passion; Entrepreneur; Life context; Person–environment fit; Performance; Creative and cultural industries